Adolescence Student Behavioral Engagement In Mathematics Class - Hidayat, Dylmoon; Kim, Tina; Listiani, Tanti; Setianingsih, Agustina Reni (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2019)
Mathematics becomes one of many subjects which shows low student engagement. This paper aims to understand students’ attitudes toward school and mathematics, the impact of student behavioral engagement, influential factors, obstacles in promoting student behavioral engagement, and how to promote student behavioral engagement. Students’ interests of school decrease in high school. Behavioral engagement impacts academic achievement, meaning of learning, and self-esteem. Influential factors of student behavioral engagement are motivation, the role of parents and teachers, and peer support. Obstacles in promoting student behavioral engagement are building intrinsic motivation, teachers’ beliefs about student behavioral engagement, and parental styles. Some ways to promote student behavioral engagement are using various teaching method, keeping optimal learning environment, and focusing on peer. Conclusion and suggestion emphasize on the role of teachers in their authority in the class and cooperate with parents.